Utilisation of magnetic saliency for sensorless-control of permanent-magnet synchronous motors - Reill, Josef; Piepenbreier, Bernhard; Hahn, Ingo (SPEEDAM 2010, 2010)
This paper presents a new method for sensorless control of permanent magnet synchronous machines (PSM) in low speed and standstill region. Actually, there exist many solutions for speed controlled applications via interpretation of the voltage equations of the PSM. There are some well known algorithms to handle sensorless operation up to standstill, too. Most of these methods use a high frequency signal and some kind of filter technique for demodulation. In this paper a new frequency domain based algorithm is proposed. The main advantage of the new strategy is the precise separation of the fundamental wave and hf-signal and avoidance of conventional filters. For phaselag reasons all filter techniques suffer from the demand for high sampling rates. The presented algorithm is compared with known methods by far better applicable to conventional industry power-converters that often have switching frequencies limited to 8 kHz. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.utilis
Keywords: Sensorless control; Signal injection; Vector control